2019
DOI: 10.1016/j.amsu.2019.03.006
|View full text |Cite
|
Sign up to set email alerts
|

The technique of story-telling in thyroid diseases including surgery; useful or not

Abstract: Introduction In the modern day busy clinical practice, the communication between patient/relative and caregiver is at a minimal level. The patients and relatives feel apprehensive when advised about surgical/interventional treatment. Storytelling is such a technique of health communication made in common man language and can operate in a virtual environment. This study aims to unveil the efficacy of storytelling technique on patients undergoing Hemithyroidectomy for benign cytology. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Consequently, the findings verified the mechanism of both informativeness and persuasiveness of a respondent in the context of the COVID-19 vaccine is explained through both central and peripheral routes in which the mechanism is based on ELM [ 16 ]. Moreover, the finding was in line with several past studies that showed how an individual was able to grasp critical information including related to healthcare through storytelling and experience sharing [ 45 , 46 ]. According to Briant et al (2016), experience sharing focuses on storytelling where the emotional connection enabled people to appreciate other stories and garner the information from the story.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consequently, the findings verified the mechanism of both informativeness and persuasiveness of a respondent in the context of the COVID-19 vaccine is explained through both central and peripheral routes in which the mechanism is based on ELM [ 16 ]. Moreover, the finding was in line with several past studies that showed how an individual was able to grasp critical information including related to healthcare through storytelling and experience sharing [ 45 , 46 ]. According to Briant et al (2016), experience sharing focuses on storytelling where the emotional connection enabled people to appreciate other stories and garner the information from the story.…”
Section: Discussionsupporting
confidence: 90%
“…Experience-based communication in the context of health communication refers to the role of experience as a central core in communication information based on storytelling techniques [ 45 ]. Scholars have reported that communication via storytelling is becoming more important, especially in the era of social media [ 46 ]. The power of storytelling as a health promotion tool is based on the ability of the storyteller to create an emotional connection that not only enables information sharing but also creates emotional benefit and therapeutic effects [ 47 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…We found that most Indian women were not aware of BSE except if any family member had suffered from breast cancer 14 , 19 and so a combination of both animation video and simulation model may provide better results. Here, where the interaction time between the patient and the consultant is suboptimal 20 , it may be problematic for surgeons to teach BSE to women, which takes 12–15 min.…”
Section: Discussionmentioning
confidence: 91%
“…Both fictional and traditional storytelling have been used for health teaching. Fictional storytelling was used to communicate health messages (Briant et al, 2016; Frank et al, 2015; Kepka et al, 2012; Larkey & Gonzalez, 2007; Larkey et al, 2009; Moghimian et al, 2019; Moran et al, 2016; Sabaretnam et al, 2019) and to address cancer prevention, targeting specific ethnic populations (Kepka et al, 2012; Lamb et al, 2018; Larkey & Gonzalez, 2007; Larkey et al, 2009; Larkey et al, 2015). Examples include a story about a Hispanic family discussing with their father the benefits and risks of colorectal cancer screening (Larkey et al, 2009) and the story of a woman from rural India who finds she has a thyroid tumor (Sabaretnam et al, 2019).…”
Section: Synthesis Of Existing Sciencementioning
confidence: 99%
“…Theoretically, as listeners engage with the story, they identify with the characters and reflect on their own life situations (Lee et al, 2016). The specific cultures targeted by storytelling included Hispanic (Kepka et al, 2012; Larkey & Gonzalez, 2007; Larkey et al, 2009; Larkey et al, 2015; Moran et al, 2016; Njeru et al, 2015); African American (Bertera, 2014; Houston et al, 2011; Houston et al, 2017); Native American (DeBruyn et al, 2020); Somali (Wieland et al, 2017); rural Vietnamese (Nguyen et al, 2017; Nguyen et al, 2018); Bangladeshi (Greenhalgh et al, 2011); Hindi (Sabaretnam et al, 2019); and Colombian (Lamb et al, 2018). To ensure cultural integration, many researchers described development of the storytelling interventions using qualitative methods such as interviews and focus groups (Fix et al, 2012; Greenhalgh et al, 2005; Kepka et al, 2012).…”
Section: Synthesis Of Existing Sciencementioning
confidence: 99%